PENDIDIKAN AGAMA ISLAM BAGI ANAK DALAM KELUARGA NELAYAN DI DESA BAKONGAN (ANALISIS PERSPEKTIF FATHERLESS) - Nurmila; Saifullah; Safrina Ariani; Maulana Rizki Aulianda (IMTIYAZ: Jurnal Ilmu Keislaman, 2026)
The father's work conditions as a fisherman that require being at sea for long periods of time cause limitations in the father's physical and psychological presence in family life. This study aims to: (1) Determine the pattern of children's religious education in fishing families; (2) Determine the symptoms of fatherlessness that appear in religious education; and (3) Analyze the impact of father's absence on morals in children in Bakongan Village. This study uses a qualitative method with a descriptive-analytical approach. Data collection techniques through observation, documentation, and in-depth interviews with informants consisting of ustad meunasah, fishermen, fishermen's wives, Islamic Religious Education teachers, village officials, and 6th grade elementary school students. The results of the study show that: (1) The pattern of religious education in Bakongan Village is dominated by the role of the mother (mother-centered) and full delegation to non-formal institutions such as TPA/Meunasah due to the father's limited time. (2) Symptoms of fatherlessness that appear include the absence of a male authority figure in accompanying practical worship and the loss of direct role models from father figures in daily religious life. (3) The impact of a father's absence significantly affects a child's morals, especially in the aspects of independent religious discipline, honesty, and emotional control.